The therapeutic effect of swallow training with a xanthan gum-based thickener in addition to classical dysphagia therapy in Chinese patients with post-stroke oropharyngeal dysphagia: A randomized controlled study - Yao Wang; Jie Zhang; Hui-Min Zhu; Can-Ping Yu; Yan Bao; Xiao-Fang Hou; Shao-Chun Huang (Annals of Indian Academy of Neurology, 2023)
Objective: In patients with post-stroke oropharyngeal dysphagia (PSOD), classical dysphagia therapy (CDT) continues to provide unsatisfactory outcomes and makes it challenging for them to remove the nasal feeding tube. Increasing bolus viscosity helps prevent aspiration in PSOD. However, conventional starch thickeners enhance post-digestion residue. This study aims to evaluate the efficacy of swallow training with xanthan gum-based thickener (XGT) (Softia G, NUTRI Co., Ltd., Yokkaichi, Japan) additional to CDT in Chinese PSOD patients with a nasogastric tube when compared to CDT alone. Methods: Patients with PSOD who had a nasogastric tube were randomly assigned to either the experimental group (E-group) or the control group (C-group) in this randomized controlled, single-blind, parallel-group study. Both groups received CDT for 4 weeks. The E-group cases received additional swallow training with a Softia G-prepared hydrogel training material. The Functional Oral Intake Scale (FOIS) and modified volume-viscosity swallow test (M-VVST) for swallowing safety and efficacy according to adjusted Chinese dietary habits were administered before and after treatment. Post-training, both groups' nasogastric tube removal rates were calculated. Results: One hundred sixty-seven participants (E-group: 82 and C-group: 85) completed the study. The E-group's median score of FOIS improved significantly than the C-group after training (median = 5 vs. 3, P < 0.001). The incidence of coughing, voice changes, oxygen desaturation of 3% or more, pharyngeal residue and piecemeal deglutition in the E-group was significantly lower than that in the C-group (P < 0.05). The E-group had 100% nasogastric tube removal, while the C-group had 28.24% (P < 0.001). Conclusion: Swallow training with XGT Softia G in addition to CDT can promote swallowing safety and efficacy in Chinese patients with PSOD more effectively than CDT alone.